2014
DOI: 10.1177/0194599814541629a15
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Fractures in Children and Adolescents: Mechanisms of Injury and Efficacy of Closed Reduction

Abstract: Objectives: (1) Determine the most common causes of traumatic nasal deformities referred to pediatric otolaryngology. (2) Examine the efficacy of closed reduction of nasal fractures in children and adolescents based on the parents’ and surgeon’s ratings of post-reduction nasal symmetry. Methods: Case series and chart review within an urban pediatric otolaryngology practice. Results: One hundred cases of traumatic nasal deformity met inclusion criteria over a 3-year study period. The mean age at presentation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…This may be related to the finding that the most common etiology of this deformity was trauma, most frequently due to physical violence, followed by sports related injuries, both of which more commonly involve males. 7 These data are consistent with results of previous demographic and epidemiologic studies on the Asian nose. 6 One of the patients had acquired the deformity from a previous rhinoplasty.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This may be related to the finding that the most common etiology of this deformity was trauma, most frequently due to physical violence, followed by sports related injuries, both of which more commonly involve males. 7 These data are consistent with results of previous demographic and epidemiologic studies on the Asian nose. 6 One of the patients had acquired the deformity from a previous rhinoplasty.…”
Section: Discussionsupporting
confidence: 91%
“…Together with the spreader graft, the camouflage graft, and the alar batten graft, the tip plasty done corrected the collapsed nostril and nasal ala present in the cleft lip-nose deformity. 7 Two patients had both a lower third level deviation and a middle level deviation. This includes the patient whose deformity was from a previous rhinoplasty.…”
Section: Discussionmentioning
confidence: 94%
“…In cases of greenstick fractures, the fracture segment is often not clearly identified; however, the condition of the fracture can be evaluated by checking abnormal bending or asymmetric bending on CT scans converted from two-dimensional to three-dimen- sional views. Greenstick fractures develop due to immature, soft, and resilient bone with thick and fibrous periosteum, and they may lead to incomplete repositioning of bone fragments or under-correction [8,17]. Four cases of typical greenstick or imprinted fractures were found in this study, all of which demonstrated incomplete repositioning of fracture segments into the pre-traumatic position regardless of the timing of reduction (Fig.…”
Section: Discussionmentioning
confidence: 63%
“…Previous studies of pediatric nasal fractures have investigated the incidence, etiology, treatment options, and outcomes [3,[6][7][8], but few reports have analyzed the time interval between in-…”
Section: Introductionmentioning
confidence: 99%